Genomic connectivity and future climate suitability of the Caribbean king crab (Maguimithrax spinosissimus) highlight its potential for coral reef restoration - Pedro A. Peres; Natalie A. Whitaker-Allen; Mark J. Butler; Heather D. Bracken-Grissom (Conservation Genetics, 2026)

Investigating the origins of quarry populations of the Caribbean King Crab (Maguimithrax spinosissimus) to inform coral reef recovery efforts in the Florida Keys, Florida (USA) - Natalie A. Whitaker-Allen; Pedro A. Peres; Mark J. Butler; Heather D. Bracken-Grissom (Coral Reefs, 2026)

Divergent Selection on Dispersal Targets Chemosensory and Neuronal Genes in Tribolium castaneum - Michael D. Pointer; Will J. Nash; Lewis G. Spurgin; Mark McMullan; Simon Butler; David S. Richardson (Molecular Ecology, 2026)
Dispersal is key to the life history, ecology and evolution of many organisms and important in pest invasiveness. However, the genetic architecture underlying variation in dispersal behaviour remains poorly understood outside of a few model species. We investigated the genomic basis of dispersal using artificial selection on replicated lines of Tribolium castaneum , a flour beetle, an emergent model system and an economically important agricultural pest. Combining whole‐genome resequencing with population‐level genotype–phenotype association analysis, we identify nine genomic regions and 42 genes associated with selection on dispersal. Identified candidate genes were significantly enriched for functions related to neuronal structure and function, as well as chemosensory behaviour and mating, suggesting that variation in dispersal is mediated by neural and chemosensory pathways. Our results demonstrate that dispersal propensity has a polygenic basis and support an interaction between dispersal and mating ecology in this system. These findings contribute to a deeper understanding of the genetic mechanisms driving dispersal evolution and its role in shaping eco‐evolutionary dynamics.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Diversity, non-additive effects, and functional redundancy drive sponge community filtration in a shallow, tropical ecosystem - Mark J. Butler (Journal of Experimental Marine Biology and Ecology, 2025)

Freshwater fish condition responses to hydrological disturbance are species‐ and scale dependent - Maxwell C. Mallett; Jason D. Thiem; Gavin L. Butler; Luke Carpenter‐Bundhoo; Mark J. Kennard (Journal of Fish Biology, 2025)
Modification of river flows is a major cause of freshwater fish population declines in many parts of the world. Identifying the precise mechanisms of these declines represents a significant challenge, as a range of stressors can simultaneously impact various components of fish health, fitness and population dynamics. Here we investigate the role of river flows and other biophysical factors on spatio‐temporal variation in freshwater fish body condition in Australia's highly modified Murray‐Darling Basin using three widely distributed native (Murray cod Maccullochella peelii , golden perch Macquaria ambigua and bony herring Nematalosa erebi ) and one introduced (common carp Cyprinus carpio ) species. Our aim was to uncover drivers of spatio‐temporal variation in fish condition at two spatial extents: at the basin scale, utilising a flow regime disturbance index, and at the river‐valley scale, employing individual flow gauge data to assess responses in fish condition to multiple measures of antecedent (365 day) flow. Linear mixed effects modelling revealed that at the basin scale, M. peelii and M. ambigua were in better condition in rivers with lower flow regime disturbance, and temporal trends in the condition of N. erebi , C. carpio and M. peelii reflected boom and bust dynamics related to wet and dry climate periods. At the river‐valley scale, mean antecedent daily flow magnitude was significantly positively related to the condition of M. peelii , M. ambigua and C. carpio , whereas the number of high‐flow days was negatively related to condition of N. erebi . Our study demonstrates that a simple body condition index calculated from routinely collected length–weight data is sensitive to multiple measures of hydrological disturbance in river systems that experience substantial temporal and spatial variability. We emphasise that studies considering multiple spatial scales are important for understanding complex scale‐dependent mechanisms influencing fish condition.

Competition for waterborne food resources among tropical shallow‐water sponges - Mark J. Butler; Steven E. McMurray; Joseph R. Pawlik (Ecology, 2025)
A recurrent theme in marine ecology is that the community dynamics of sessile, suspension‐feeding animals is primarily limited by the availability of space, but in some habitats, filtration by these organisms may locally deplete water column resources, setting the stage for exploitative competition for food. We examined filtration by sponge assemblages in the shallow waters (~2 m depth) of Florida Bay (Florida, USA), where water residence times are often high and filtration by dense communities of sponges was hypothesized to deplete the water column of food, primarily picoplankton and dissolved organic matter (DOM). We transplanted three sponge species into replicate locations that differed by an order of magnitude in natural sponge community biomass. Sponge transplants were clones, enabling us to control for sponge genotype effects across all sites. The growth of sponge clones was recorded seasonally for 18–30 months. Growth of transplants placed in areas devoid of sponges was 10 times greater than growth in areas with dense sponge communities and three times greater than growth in areas with average sponge biomass. Sponge mortality was similar regardless of background sponge density. Measurements of picoplankton, DOM, and PO 4 concentration confirmed an inverse relationship with sponge community biomass, whereas nitrogen concentrations in seawater were highest where sponge species replete with nitrogen‐fixing symbiotic microbial communities were most abundant. This is striking evidence that filtration of waterborne resources by sponges in shallow, coastal environments can deplete those resources sufficiently to cause exploitative competition that limits sponge growth.

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Gastric mill ossicles record chronological age in the Caribbean spiny lobster (Panulirus argus) - Emily Hutchinson; Thomas R. Matthews; Erica Ross; Samantha Hagedorn; Mark J. Butler (Fisheries Research, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Accumulation and transport of nutrient and pollutant elements in riparian soils, sediments, and river waters across the Thames River Watershed, Connecticut, USA - Mark J. Butler; Brian C. Yellen; Oluyinka Oyewumi; William Ouimet; Justin B. Richardson (Science of The Total Environment, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Correction to: Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)

Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)
Pumas ( Puma concolor ) were eliminated from most of the eastern USA a century ago. In the past couple of decades, their recovery in the West has increased puma dispersal into the Midwest, with some individuals even traveling to the East Coast. We combined published expert opinion data and a habitat suitability index in an analysis that identified 17 areas in the Upper Midwest, Ozarks, Appalachia, and New England that could potentially host puma populations in the future. Thirteen of these were larger than 10,000 km 2 and so likely to ensure a puma population’s long-term genetic health. Further, we quantified patch size, human density, livestock density, percent public land, and a sociocultural index reflecting wildlife values for comparing patches, as well as present a summary of current legislation relevant to puma management in the East. Our work may be useful in identifying suitable areas to restore pumas based not only on the quality of their biophysical habitat, but also on social values conducive to puma-human coexistence.

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Classifying 3-D Models of Coral Reefs Using Structure-From-Motion and Multi-View Semantic Segmentation - Jordan Pierce; Mark J. Butler; Yuri Rzhanov; Kim Lowell; Jennifer A. Dijkstra (Frontiers in Marine Science, 2021)
Benthic quadrat surveys using 2-D images are one of the most common methods of quantifying the composition of coral reef communities, but they and other methods fail to assess changes in species composition as a 3-dimensional system, arguably one of the most important attributes in foundational systems. Structure-from-motion (SfM) algorithms that utilize images collected from various viewpoints to form an accurate 3-D model have become more common among ecologists in recent years. However, there exist few efficient methods that can classify portions of the 3-D model to specific ecological functional groups. This lack of granularity makes it more difficult to identify the class category responsible for changes in the structure of coral reef communities. We present a novel method that can efficiently provide semantic labels of functional groups to 3-D reconstructed models created from commonly used SfM software (i.e., Agisoft Metashape) using fully convolutional networks (FCNs). Unlike other methods, ours involves creating dense labels for each of the images used in the 3-D reconstruction and then reusing the projection matrices created during the SfM process to project semantic labels onto either the point cloud or mesh to create fully classified versions. When quantitatively validating the classification results we found that this method is capable of accurately projecting semantic labels from image-space to model-space with scores as high as 91% pixel accuracy. Furthermore, because each image only needs to be provided with a single set of dense labels this method scales linearly making it useful for large areas or high resolution-models. Although SfM has become widely adopted by ecologists, deep learning presents a steep learning curve for many. To ensure repeatability and ease-of-use, we provide a comprehensive workflow with detailed instructions and open-sourced the programming code to assist others in replicating our methodology. Our method will allow researchers to assess precise changes in 3-D community composition of reef habitats in an entirely novel way, providing more insight into changes in ecological paradigms, such as those that occur during coral-algae shifts.

Response of Fish and Invertebrate Larvae to Backreef Sounds at Varying Distances: Implications for Habitat Restoration - Emily R. Anderson; Jack Butler; Mark J. Butler (Frontiers in Marine Science, 2021)
Underwater sound is used by many marine larvae to orient to coastal habitats including backreef, sponge-dominated hardbottom habitat in the Florida Keys (FL, United States)—a particularly “noisy” coastal habitat. However, the distance over which acoustic cues are attractive to settlement-stage larvae is generally unknown. We examined this phenomenon in a region of the Florida Keys where mass sponge die-offs have diminished both underwater soundscapes and larval settlement. The absence of pronounced hardbottom-associated sound over such a large area allowed us to experimentally test in situ the response of fish and invertebrate larvae to broadcasted sounds at different distances from their source. We first measured the signal-to-noise ratio of healthy hardbottom habitat soundscapes broadcast from an underwater speaker at seven distances to determine the maximum range of the signal. Based on those results, larval collectors were then deployed at 10, 100, 500, and 1,000 m from speakers broadcasting sounds recorded at either degraded or healthy hardbottom sites for five consecutive nights during each of three new and full moon periods in summer/fall 2019. Larval settlement onto those collectors was affected by lunar phase and soundscape type, but varied among species. In most cases, the effect was small and not likely to be ecologically significant. The absence of a strong larval settlement response to a sound cue lies in contrast to results from other studies. We suspect that the small (<500 m) radius of the broadcasted soundscapes may have limited the magnitude of the larval response to locally available larvae whose abundance may have been low because the experiment was conducted within a large, relatively quiet seascape. If true, it is possible that planktonic larvae may require a series of acoustic “sign-posts,” perhaps in combination with other cues (e.g., chemical), to successfully orient to distant nursery habitats. Although habitat restoration efforts may be able to restore healthy soundscapes, the typically small size and number of restoration sites may limit the range of the acoustic cue and thus larval attraction to restored habitats.

Trace metals and metalloids in peri-urban soil and foliage across geologic materials, ecosystems, and development intensities in Southern California - Trevor J. Mackowiak; Ivan C. Mischenko; Mark J. Butler; Justin B. Richardson (Journal of Soils and Sediments, 2021)

Conserving spawning stocks through harvest slot limits and no‐take protected areas - Gaya Gnanalingam; Holly Gaff; Mark J. Butler (Conservation Biology, 2020)
The key to the conservation of harvested species is the maintenance of reproductive success. Yet for many marine species large, old, individuals are targeted despite their disproportionate contribution to reproduction. We hypothesized that a combination of no‐take marine protected areas (MPAs) and harvest slot limits (maximum and minimum size limits) would result in the conservation of large spawning individuals under heavy harvest. We tested this approach under different harvest intensities with a 2‐sex, stage‐structured metapopulation model for the Caribbean spiny lobster ( Panulirus argus ). P. argus is intensively harvested in the Caribbean, and in many localities large, mature individuals no longer exist. No‐take MPAs and harvest slot limits combined, rebuilt and maintained large mature individuals even under high harvest pressure. The most conservative model (a 30% MPA and harvest slot limit of 75–105 mm) increased spawner abundance by 5.53E 12 compared with the fishing status quo at the end of 30 years. Spawning stock abundance also increased by 2.76–9.56E 12 individuals at a high harvest intensity over 30 years with MPAs alone. Our results demonstrate the potential of MPAs and harvest slot limits for the conservation of large breeding individuals in some marine and freshwater environments. Decisions on which management strategy best suits a fishery, however, requires balancing what is ecologically desirable with what is economically and socially feasible.

Chromium, manganese, nickel, and cobalt mobility and bioavailability from mafic-to-ultramafic mine spoil weathering in western Massachusetts, USA - Justin A. Mistikawy; Trevor J. Mackowiak; Mark J. Butler; Ivan C. Mischenko; Richard S. Cernak; Justin B. Richardson (Environmental Geochemistry and Health, 2020)

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Potential Impacts of Everglades Restoration on Lobster and Hard Bottom Communities in the Florida Keys, FL (USA) - Mark J. Butler; Thomas W. Dolan (Estuaries and Coasts, 2017)

Biophysical connectivity explains population genetic structure in a highly dispersive marine species - Nathan K. Truelove; Andrew S. Kough; Donald C. Behringer; Claire B. Paris; Stephen J. Box; Richard F. Preziosi; Mark J. Butler (Coral Reefs, 2017)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Genetic evidence from the spiny lobster fishery supports international cooperation among Central American marine protected areas - Nathan K. Truelove; Sarah Griffiths; Kim Ley-Cooper; James Azueta; Isaias Majil; Stephen J. Box; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Conservation Genetics, 2015)

Host behavior alters spiny lobster–viral disease dynamics: a simulation study - Thomas W. Dolan; Mark J. Butler IV; Jeffrey D. Shields (Ecology, 2014)
Social behavior confers numerous benefits to animals but also risks, among them an increase in the spread of pathogenic diseases. We examined the trade‐off between risk of predation and disease transmission under different scenarios of host spatial structure and disease avoidance behavior using a spatially explicit, individual‐based model of the host–pathogen interaction between juvenile Caribbean spiny lobster ( Panulirus argus ) and Panulirus argus Virus 1 (PaV1). Spiny lobsters are normally social but modify their behavior to avoid diseased conspecifics, a potentially effective means of reducing transmission but one rarely observed in the wild. We found that without lobster avoidance of diseased conspecifics, viral outbreaks grew in intensity and duration in simulations until the virus was maintained continuously at unrealistically high levels. However, when we invoked disease avoidance at empirically observed levels, the intensity and duration of outbreaks was reduced and the disease extirpated within five years. Increased lobster (host) spatial aggregation mimicking that which occurs when sponge shelters for lobsters are diminished by harmful algal blooms, did not significantly increase PaV1 transmission or persistence in lobster populations. On the contrary, behavioral aversion of diseased conspecifics effectively reduced viral prevalence, even when shelters were limited, which reduced shelter availability for all lobsters but increased predation, especially of infected lobsters. Therefore, avoidance of diseased conspecifics selects against transmission by contact, promotes alternative modes of transmission, and results in a more resilient host–pathogen system.

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Mate choice and sperm limitation in the spotted spiny lobster, Panulirus guttatus - Denice N. Robertson; Mark J. Butler (Marine Biology Research, 2013)

Herbivory by the Caribbean king crab on coral patch reefs - Mark J. Butler; Angela M. Mojica (Marine Biology, 2012)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Disease avoidance influences shelter use and predation in Caribbean spiny lobster - Donald C. Behringer; Mark J. Butler (Behavioral Ecology and Sociobiology, 2010)

Relationships Between Major Ownerships, Forest Aboveground Biomass Distributions, and Landscape Dynamics in the New England Region of USA - Daolan Zheng; Linda S. Heath; Mark J. Ducey; Brett Butler (Environmental Management, 2010)

Behavioral enhancement of onshore transport by postlarval Caribbean spiny lobster (Panulirus argus) - Jason S. Goldsteina; Mark J. Butler (Limnology and Oceanography, 2009)
We conducted a series of laboratory experiments to examine the orientation, settlement, and metamorphosis of Caribbean spiny lobster ( Panulirus argus ) pueruli (postlarvae) in response to cues characteristic of their nursery in back‐reef tropical lagoons. Our results suggest that pueruli were attracted to coastal water sources and the metabolites of red macroalgae ( Laurencia spp.) when compared with oceanic water and artificial seawater treatments. Pueruli were not attracted to waterborne cues from sea grass, were repelled by hypersaline or hyposaline water, and discerned coastal cues from water collected as far as 30 km offshore from the reef. We also conducted experiments to examine the settlement behavior of pueruli in response to different substrates and hydrostatic pressures. Pueruli only settled at pressures equivalent to depths ≪5 m, which is where most settlement occurs in the field; settlement behavior was further enhanced by the presence of red macroalgae. Coastal water or artificial seawater containing red macroalgae metabolites hastened puerulus development and molting to the benthic juvenile stage by 20‐30% compared with those exposed to artificial seawater. Collectively, our results demonstrate that spiny lobster pueruli use chemical and pressure cues during onshore transport and selection of settlement habitat, highlighting the important role of behavioral responses to physical cues in the recruitment of this species.

Regional characterisation of hard‐bottom nursery habitat for juvenile Caribbean spiny lobster (Panulirus argus) using rapid assessment techniques - Rodney D. Bertelsen; Mark J. Butler; William F. Herrnkind; John H. Hunt (New Zealand Journal of Marine and Freshwater Research, 2009)
Shallow, hard‐bottom habitat constitutes approximately 30% of the coastal waters of south Florida, United States, yet it is a chronically understudied feature of the marine seascape in this region. In this study, we characterised the general biogeographic and structural features of shallow benthic hard‐bottom communities in the Florida Keys, and related those to the abundance of juvenile Caribbean spiny lobster (Panulirus argus) , the target of one of Florida's most economically valuable fisheries. We used rapid assessment techniques to survey more than 100 hard‐bottom sites in the Florida Keys to estimate the percentage bottom coverage of vegetation (seagrass and macroalgae) and the abundance of sponges, octocorals, hard corals, and other crevice‐bearing structures, as well as the abundance of juvenile lobsters. Using a multivariate statistical approach, we evaluated the relationship between habitat and size‐specific juvenile lobster abundance and quantitatively verified the existence of six generally accepted biogeographic subregions. Although the types of hard‐bottom shelters used by juvenile lobsters varied somewhat among these subregions, in all regions, branching‐candle sponges and octocorals were under‐used by lobsters, whereas loggerhead sponges, coral heads, and solution holes were over‐used (i.e., used more frequently than expected based on their availability). There was also an ontogenetic transition in the shelter preference of juvenile lobsters; small juveniles tended to occupy a variety of sponges, whereas large juveniles preferred hard structures such as coral heads and solution holes. This study yields the first quantitative biogeographic description of hard‐bottom communities of the Florida Keys, and confirms the suspected relationship between the structural features of hard‐bottom habitat and the value of these communities as nurseries for juvenile spiny lobster.

Is seagrass an important nursery habitat for the Caribbean spiny lobster, panulirus argus , in Florida? - Donald C. Behringer; Mark J. Butler; William F. Herrnkind; John H. Hunt; Charles A. Acosta; William C. Sharp (New Zealand Journal of Marine and Freshwater Research, 2009)
Caribbean spiny lobster (Panulirus argus) settle preferentially in macroalgal‐covered hard‐bottom habitat, but seagrass is more prevalent in Florida (United States) and the Caribbean, so even low settlement of lobsters within seagrass could contribute substantially to recruitment if post‐settlement survival and growth were high. We tested the role of seagrass and hard‐bottom habitats for P. argus recruitment in three ways. We first explored possible density‐dependent regulation of early benthic juvenile lobster survival within cages deployed in seagrass and hard‐bottom habitats. Second, we compared settlement and survival of P. argus in both habitats, by comparing the recovery of microwire‐tagged early benthic juveniles from patches of seagrass and hard‐bottom. Finally, we assessed the relative abundance of juvenile lobsters in each habitat by deploying artificial structures in seagrass sites and compared these data with data from similar deployments of artificial structures in hard‐bottom habitat in other years. More early benthic juvenile lobsters were recovered from cages placed in hard‐bottom than in seagrass, but mortality of the early benthic life stage was high in both habitats. In regional surveys, the mean number of lobsters recovered from artificial shelters deployed within seagrass was lower than in any year that we sampled hard‐bottom, indicating that fewer lobsters reside naturally in seagrass, particularly large juveniles >40 mm carapace length. The greater abundance (and likely survival) of juvenile P. argus that we observed in hard‐bottom habitat as opposed to seagrass, combined with previous studies demonstrating that postlarval P. argus are attracted to, settle in, and metamorphose more quickly in red macroalgae, confirm that macroalgae‐dominated hard‐bottom habitat appears to be the preferred and more optimal nursery for Caribbean spiny lobster.

Farmers’ objectives toward their woodlands in the upper Midwest of the United States: implications for woodland volumes and diversity - W. Keith Moser; Earl C. Leatherberry; Mark H. Hansen; Brett J. Butler (Agroforestry Systems, 2009)

Wild turkey (Meleagris gallopavo) detectability from helicopters and ramifications for estimating abundance - Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Stephen J. DeMaso (European Journal of Wildlife Research, 2008)

Stable isotope analysis of production and trophic relationships in a tropical marine hard-bottom community - Donald C. Behringer; Mark J. Butler (Oecologia, 2006)

Feeding ecology of juvenile spiny lobster, Panulirus interruptus, on the Pacific coast of Baja California Sur, Mexico - Verónica Castañeda‐Fernández‐de‐Lara; Elisa Serviere‐Zaragoza; Sergio Hernández‐Vázquez; Mark J. Butler (New Zealand Journal of Marine and Freshwater Research, 2005)
Many aspects of the early life history of the red lobster Panulirus interruptus are little known, including the relationship between habitat structure, food resource availability, and nutrition of juveniles. We investigated the spatial and temporal differences in food intake, diet composition, and nutritional condition of juveniles at two sites along the Pacific coast of the Baja California Peninsula (Mexico) with contrasting oceanographic and biological conditions. One site (Arvin) is located inside a protected bay, Bahía Tortugas, where the waters are cooler and temperate seagrasses and macroalgae are the dominant benthic flora. The second site (Queen) in Bahía Sebastían Vizcaíno was located along a more open coastline where seawater temperatures were higher and the benthic flora more indicative of warmer seas. At both sites, we randomly sampled epifauna within vegetated habitats to estimate the seasonal availability of food resources for juvenile lobsters from autumn 2001 until summer 2002. Concurrently, we used traps to sample P. interruptus juveniles for stomach content analysis. At both sites, Amphipoda, Gastropoda, and Polychaeta dominated the epifauna assemblages, as determined by an Index of Importance. Juvenile P. interruptus primarily consumed crustaceans (mostly amphipods and isopods) and vegetal material (surf‐grass Phyllospadix spp. and calcareous algae), but their food spectrum was wide. Manly's Index of Resource Selection indicated that lobsters preferred some prey (e.g., Brachyurans) over others despite their low Index of Importance. Despite marked differences in the types of food and their availability between sites, there were no significant differences in the nutritional condition (e.g., relative weight of the digestive gland) of lobsters at the two sites. However, the nutritional condition of lobsters was effected during some seasons. In particular, their condition deteriorated during the spring (April 2002) at Arvin, as did the proportion of individuals with empty stomachs. This study shows the feeding adaptation capacity of the juvenile California spiny lobster P. interruptus to different environmental conditions prevalent in Centre Baja California Peninsula.

A comparison of horizontally and vertically deployed aquatic invertebrate activity traps - Miles J. Muscha; Kyle D. Zimmer; Malcolm G. Butler; Mark A. Hanson (Wetlands, 2001)

Sperm economy and limitation in spiny lobsters - A. B. MacDiarmid; Mark J. Butler IV (Behavioral Ecology and Sociobiology, 1999)

Adaptive strategies that reduce predation on Caribbean spiny lobster postlarvae during onshore transport - Charles A. Acosta; Mark J. Butler (Limnology and Oceanography, 1999)
Like many marine species with meroplanktonic larvae, the Caribbean spiny lobster ( Panulirus argus ) has a postlarval stage that moves from the oceanic plankton to inshore nurseries only under specific environmental conditions (i.e., at night, in the surface water layer, on the flood tide, and during new moon), presumably to avoid predation or to enhance onshore transport. Using field and mesocosm experiments, we compared predation on planktonic postlarvae swimming at night near the surface and bottom over coastal habitats along typical offshore–inshore transport paths and determined whether predation rates differed between lunar periods (new moon vs. full moon) and with prey density (i.e., predator encounter rates). We also measured predation on transparent (newly settled) and pigmented (nearing metamorphosis) postlarvae sheltering in coral reef, seagrass, and macroalgal habitats during the day. We measured predation on postlarvae swimming near the surface and bottom along typical offshore–inshore transport paths (i.e., coral reefs, coastal lagoon, and bay) by tethering postlarvae to floats that drifted on the nightly flood tide during new moon. To test the hypothesis that new‐moon transport of postlarvae may have evolved as a means to avoid higher predation under the bright full moon, we repeated the pelagic tethering experiments at the reef and in the bay during full moon. Mortality was highest over coral reefs regardless of lunar phase, but it was lower nearshore, especially in the bay near the surface and during new moon. Predation on benthic, recently settled transparent postlarvae and pigmented postlarvae (nearing metamorphosis) was also higher when tethered on the reef as opposed to vegetated habitats in the lagoon and bay. In experimental mesocosms, planktivorous fish were equally efficient at consuming postlarvae under new‐ and full‐moon conditions when postlarval density was high, as it is in the constricted water column over the reefs. However, when postlarvae were less dense, mortality was significantly lower during new moon. Collectively, these results indicate that several behavioral traits exhibited by postlarval spiny lobsters, including inshore migration during the darkest lunar phase, use of surface waters, and settlement in vegetated habitats, reduce their risk of predation, particularly in the shallow bay. No single behavioral strategy is universally advantageous across all coastal habitats, but combined, they are an effective means to reduce predation across heterogeneous environments that postlarvae must transit during recruitment.